2016
DOI: 10.5367/ihe.2016.0296
|View full text |Cite
|
Sign up to set email alerts
|

Students' Attitudes toward a Group Coursework Protocol and Peer Assessment System

Abstract: This paper addresses a knowledge gap by presenting an empirical investigation of a group coursework protocol and peer assessment system (GCP&PAS) used in a UK university to support postgraduate marketing students in their assessed group activities. The aim of the research was to examine students' understanding of the GCP&PAS and their attitudes towards assessed group coursework and peer assessments generally. The study also sought to identify any differences in such attitudes as a result of gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…In a study of 280 students, Wen and Tsai (2006) found that students had a positive attitude about peer assessment at the individual level. Other research reports that students also have a generally favorable view toward peer assessment of in-person group projects (Moraes, Michaelidou, & Canning, 2016). Peer group grading helps students glean insights from other students and provides an extended layer of perceived fairness in the process (Luo, Robinson, & Park, 2014).…”
Section: Perceived Fairnessmentioning
confidence: 99%
“…In a study of 280 students, Wen and Tsai (2006) found that students had a positive attitude about peer assessment at the individual level. Other research reports that students also have a generally favorable view toward peer assessment of in-person group projects (Moraes, Michaelidou, & Canning, 2016). Peer group grading helps students glean insights from other students and provides an extended layer of perceived fairness in the process (Luo, Robinson, & Park, 2014).…”
Section: Perceived Fairnessmentioning
confidence: 99%
“…The study found out that group work has positive impact in addressing the misconceptions of light comparing to the traditional way of teaching. Thus it disagrees with a number of other studies that were resistance to the use of group-work [59,60,61,62]. Some of the negative impacts of the group work as mentioned in those articles were, it interrupts the flow of the lesson, slow down the coverage of the curriculum, it involves the loss of classroom control, increased noise, disruption and off task behaviour, beliefs that children did not work together and are unable to learn from one another.…”
Section: Impacts Of Group Workmentioning
confidence: 84%
“…Lastly, students have also noted that some of their negative preconceptions about team work are based on their past experiences regarding the difficulties in managing clashing scheduling and other conflicts with their teammates (Capdeferro & Romero, 2012;Chang & Brickman, 2018;Colbeck et al, 2000;Freeman & Greencare, 2011;Marks & O'Connor, 2013;McCorkle et al, 1999;Opdecam & Everaert, 2018). Others have expressed explicit concern about their inability to manage conflict and misunderstandings with teammates from different backgrounds (Graves & Elsass, 2005;Harrison & Peacock, 2009;Mak et al, 2014;Moraes et al, 2016;Rienties et al, 2014;Strauss et al, 2014).…”
Section: The Realities Of Team Work In Business Coursesmentioning
confidence: 99%